The Effect of Digital Payment Implementation and Transaction Security on the Development of MSMEs with Financial Stability as a Mediating Variable(A Study of SMEs in Sorong City) - Wenty Kurniati; Yowel Oktofianus Gifelem (Universitas 17 Agustus 1945 Semarang, 2026)
This study analyzes the effect of digital payment implementation (X1) and transaction security (X2) on SME development (Y) with financial stability as a mediating variable (Z) in SMEs in Sorong City. This study examines the effect of digital payment implementation and transaction security on SME development with financial stability as a mediating variable. The study was conducted on MSMEs in Sorong City, Eastern Indonesia, using an explanatory quantitative approach. The data were analyzed using Partial Least Squares-based Structural Equation Modeling (SEM-PLS). The results of the study prove that the implementation of digital payments and transaction security has a positive and significant effect on financial stability. Furthermore, financial stability was found to have a positive and significant effect on MSME development, while fully mediating the effect of transaction security and partially mediating the effect of digital payment implementation on MSME development. These findings contribute to an integrated conceptual model that combines the technology acceptance paradigm with financial management theory, and provide a strategic roadmap for policymakers and implementation guidelines for MSME actors.